2019 American Heart Association Focused Update on Neonatal Resuscitation: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. Issue 24 (10th December 2019) - Escobedo, Marilyn B.; Aziz, Khalid; Kapadia, Vishal S.; Lee, Henry C.; Niermeyer, Susan; Schmölzer, Georg M.; Szyld, Edgardo; Weiner, Gary M.; Wyckoff, Myra H.; Yamada, Nicole K.; Zaichkin, Jeanette G.
Abstract : This 2019 focused update to the American Heart Association neonatal resuscitation guidelines is based on 2 evidence reviews recently completed under the direction of the International Liaison Committee on Resuscitation Neonatal Life Support Task Force. The International Liaison Committee on Resuscitation Expert Systematic Reviewer and content experts performed comprehensive reviews of the scientific literature on the appropriate initial oxygen concentration for use during neonatal resuscitation in 2 groups: term and late-preterm newborns (≥35 weeks of gestation) and preterm newborns (<35 weeks of gestation). This article summarizes those evidence reviews and presents recommendations. The recommendations for neonatal resuscitation are as follows: In term and late-preterm newborns (≥35 weeks of gestation) receiving respiratory support at birth, the initial use of 21% oxygen is reasonable. One hundred percent oxygen should not be used to initiate resuscitation because it is associated with excess mortality. In preterm newborns (<35 weeks of gestation) receiving respiratory support at birth, it may be reasonable to begin with 21% to 30% oxygen and to base subsequent oxygen titration on oxygen saturation targets. These guidelines require no change in the Neonatal Resuscitation Algorithm–2015 Update.